Does aerobic training promote the same skeletal muscle hypertrophy as resistance training? A systematic review and meta-analysis - Grgic, J.; Mcllvenna, L. C.; Fyfe, J. J.; Sabol, F.; Bishop, D. J.; Schoenfeld, B. J.; Pedisic, Z. (Sports Medicine, 2019)
Background: Currently, there are inconsistencies in the body of evidence for the effects of resistance and aerobic training on skeletal muscle hypertrophy. Objective: We aimed to systematically review and meta-analyze current evidence on the differences in hypertrophic adaptation to aerobic and resistance training, and to discuss potential reasons for the disparities noted in the literature. Methods: The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed for this review. The Downs and Black checklist was used for the assessment of methodological quality of the included studies. A random-effects meta-analysis was employed. In total, three analyses were performed: (1) for whole-muscle knee extensor data; (2) for type I fiber cross-sectional area; and (3) for type II fiber cross-sectional area. Results: The final number of included studies in the present review is 21. All studies were of good or moderate methodological quality. The meta-analysis for whole-muscle hypertrophy resulted in a significant pooled difference (p < 0.001) in responses between the aerobic training and resistance training interventions. The pooled Hedge`s g, favoring resistance over aerobic training, was 0.66 (95% confidence interval 0.41-90; I2 = 0%). The meta-analysis for type I fiber cross-sectional area data resulted in a significant pooled difference (p < 0.001) between the aerobic training and resistance training groups. The pooled Hedge`s g, favoring resistance training over aerobic training, was 0.99 (95% confidence interval 0.44-1.54; I2 = 24%). The meta-analysis of type II fiber cross-sectional area data resulted in a significant pooled difference (p < 0.001) between the aerobic training and resistance training groups. The pooled Hedge`s g, favoring resistance training over aerobic training, was 1.44 (95% confidence interval 0.93-1.95; I2 = 8%). Conclusions: The results of this systematic review and meta-analysis suggest that single-mode aerobic training does not promote the same skeletal muscle hypertrophy as resistance training. This finding was consistent with measurements of muscle hypertrophy both at the whole-muscle and myofiber levels. While these results are specific to the knee extensor musculature, it can be hypothesized that similar results would be seen for other muscle groups as well.